Transformation of Monoclonal B Lymphocytosis to Epstein-Barr Virus–Positive Large B-Cell Lymphoma With Intermediate Features Between Diffuse Large B-cell Lymphoma and Classic Hodgkin Lymphoma. Issue 5 (September 2019) - Liu, Ying; Ho, Caleb; Roshal, Mikhail; Baik, Jeeyeon; Arcila, Maria; Zhang, Yanming; Dogan, Ahmet; Xiao, Wenbin
Abstract : Abstract: Transformation of chronic lymphocytic leukemia (CLL) to an aggressive lymphoma, so-called Richter syndrome, usually includes diffuse large B-cell lymphoma and classic Hodgkin lymphoma. The transformation can be clonally related to the underlying CLL and is often Epstein-Barr virus (EBV) associated. Here we report the case of an 86-year-old woman with a newly identified CLL-like monoclonal B-lymphocytosis who developed diffuse lymphadenopathy. Biopsy of the left axillary lymph node showed EBV-positive large B-cell lymphoma with morphologic and immunophenotypic features intermediate between diffuse large B-cell lymphoma and classic Hodgkin lymphoma, so-called gray zone lymphoma. Comprehensive immunophenotypic, cytogenetic, and molecular studies demonstrate a clonal relatedness that suggests a transformation from monoclonal B-lymphocytosis to EBV + gray zone lymphoma.